Well-Aware’ QI Project: Well-Being Support Awareness for Specialty Resident Doctors in Kent - Suresh Thapaliya; Adeola Adeyemi; Eric Barratt; Rachel Daly (BJPsych Open)
Aims: Doctors in training can be at high pressure to balance the service needs with their own training needs, thus leading to a risk of burnout. Hence, supporting their wellbeing is of paramount importance to optimize their training experience. This Quality Improvement (QI) project led to an improvement in well-being support for specialty trainee psychiatrists, training in Kent, United Kingdom.